الانعكاسات الشكلية واللونية على سطح العمل الفني وأثرها في تنوع القيم الإيقاعية والتعبيرية: تجربة ذاتية في التصوير المعاصر - اليحيائية، فخرية بنت خلفان (جامعة حلوان - كلية التربية الفنية, 2015)
The current research aims to provide analytical optical done in contemporary collage work read from the perspective of self-experience of the artist. Find where convey philosophical thought of self-artist by allowing recipients and Taster chance to access the contents of the works of art that resulted from the principle of overlap between the esophagus and the audio which was awarded the business recipe homogeneity in organizing formal implicit. The researcher used descriptive analytical approach in the provision of analytical reading visual exhibition "reflection" Self-experiment through intellectual and philosophical .implications of artistic and aesthetic values analysis And provides research reading in philosophy of self-artist in the merger between the moving rhythm and tempo hard in integrated entities of bilateral artwork fixed and visual dimensions (video art) are all involved in the unified nature of form and color and texture, ensures the recipient a .sense of total unity of form and content
Keywords: التصوير -- القيم الإيقاعية -- القيم التعبيرية